Stability of HCT, HGB and RBC values in the Mute Swan (Cygnus olor) blood stored at 4°c and 24°c differs between traditional and multi-parameter automated methods - TRZECIAK, M. A.; MEISSNER, W. (Journal of the Hellenic Veterinary Medical Society, 2018)
The objective of this study was to evaluate the influence of time of sample storage, method of analysis, and storage temperature on stability of HCT, HGB, and RBC in avian blood samples. Blood samples from mute swans were stored at 24°C or 4°C. Analyses of HCT, HGB, and RBC were carried out after 5 and 25 hours after collection of blood using both traditional and Cell-Dyn 3700 analyzer methods. Storage temperature had no significant influence on HCT, HGB, and RBC values of mute swan blood. However hematological parameters obtained by the traditional method were significantly lower than the results from the analyzer. Time of storage had a significant influence on values obtained traditionally for HCT, HGB, and RBC, but did not affect results that were obtained by the multi-parameter automated method. These results indicate that the mute swan blood can be stored at both room and refrigerator temperature. However, the analysis should be performed as soon as possible, especially in the case of traditional methods. Reference intervals for this species should always include information about the method used for hemogram determination and time elapsed since the blood collection.